156k views
1 vote
The following equation 3(2x - 1) = 6(1 + 1) has infinite solutions True False​

User Shrivb
by
4.8k points

2 Answers

2 votes

Answer:

False.

Explanation:

3(2x - 1) = 6 (1+1)

3*2x - 3*1 = 6*2

6x - 3 = 12

Add 3 to both side

6x = 12+ 3

6x = 15

Divide both sides by 6

x = 15/6

x = 2.5

This equation has one solution

User Kunal
by
4.2k points
2 votes

Answer:

False

Explanation:

3(2x - 1) = 6(1 + 1)

Distribute

6x -3 = 6(2)

6x -3 = 12

Add 3 to each side

6x =15

x = 15/6

There is one solution

User Konnigun
by
4.9k points